Review of 1971/02/04 Concert of Works at Town Hall, Birmingham. Works by Lutoslawski, Prokofiev and Bartok, given by the City of Birmingham Symphony Orchestra conducted by Maurice Handford, with Shura Cherkassky as soloist. - Lloyd, Ian (Contact: A Journal for Contemporary Music (1971-1990), 1971)